Respuesta :
Answer: Option A
Step-by-step explanation:
The graph of a quadratic function is a parabola.
Find the x-coordinate of the vertex of the parabola with:
[tex]x=\frac{-b}{2a}[/tex]
In this case:
[tex]b=-12\\a=-3[/tex]
Substitute them into the formula. Then:
[tex]x=\frac{-(-12)}{2(-3)}\\\\x=-2[/tex]
Now, substitute the [tex]x=-2[/tex] into the quadratic function to find the y-coordinate of the vertex of the parabola.
Finally:
[tex]y = -3x^2 - 12x - 9\\\\y = -3(-2)^2 - 12(-2) - 9\\y=3[/tex]
The vertex is: (-2,3)
Answer:
A. (-2,3)
Step-by-step explanation:
You can write a general equation from an quadratic equation that follow:
y=ax^2+bx+c
and you can calculate the vertex (x1,y1) like:
x1=-b/2a
y1=(4ac-b^2)/4a
Then, you have y = -3x^2 - 12x - 9
where:
a=-3
b=-12
c=-9
Now you can calculate the vertex (x1,y1):
x1=-b/2a=-(-12)/(2*-3)=12/-6=-2
y1=(4ac-b^2)/4a)((4*-3*-9)-(-12^2))/(4*-3)=(108-144)/-12=3